Drones and Eucharist - Smith, Jason M. (Religions, 2019)
In the post-9/11 world, the use of drone strikes has become a critical aspect of U.S. Military strategy in the War on Terror. While the ethics of drones have been argued from a theological perspective, this essay argues that a deeper, more theoretical understanding of drones is necessary in order to mount an adequate theological response. The author argues that the particular epistemological foundations by which drone strikes are justified must be given a theological corrective and that the Eucharist is the site for such a correction. This essay ultimately argues that the Eucharist shows the epistemology that undergirds the use of drones to be severely lacking and that under the judgment of the Eucharist the use of such technology is incompatible with the identity of the Church.